2021
DOI: 10.3389/fvets.2021.606116
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and Inter-observer Variability of Computed Tomographic Measurements of the Prostate Gland in Neutered Dogs

Abstract: The purpose of this study was to evaluate the intra- and inter-observer variability of computed tomographic measurements of linear prostate dimensions in neutered dogs without signs of prostatic disease, to determine potential associations between prostatic parameters and body weight or age and to provide reference ranges. Length, width and height of the prostate gland were measured in 62 neutered dogs with no signs of prostatic disease by three observers with different levels of training. Statistically signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 20 publications
1
3
1
Order By: Relevance
“…The results of the current study are in line with a recent study comparing volumetric assessment of the prostate gland in 57 intact and 37 castrated canines, as measured using the slice addition technique in CT [18]. A study regarding linear prostatic dimensions of 62 castrated dogs, as measured on computed tomographic images, revealed a positive association between body weight and prostate dimensions, also in line with our current findings [12]. The work of Atalan et al [10] failed to illustrate a relationship between prostatic size and weight of the dog in castrated animals, which was attributed to the very small sample size of castrated dogs (17 dogs were present in the castrated dogs group) in that study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The results of the current study are in line with a recent study comparing volumetric assessment of the prostate gland in 57 intact and 37 castrated canines, as measured using the slice addition technique in CT [18]. A study regarding linear prostatic dimensions of 62 castrated dogs, as measured on computed tomographic images, revealed a positive association between body weight and prostate dimensions, also in line with our current findings [12]. The work of Atalan et al [10] failed to illustrate a relationship between prostatic size and weight of the dog in castrated animals, which was attributed to the very small sample size of castrated dogs (17 dogs were present in the castrated dogs group) in that study.…”
Section: Discussionsupporting
confidence: 92%
“…In this study the prostate volume was calculated based on three linear dimensions of the prostate gland as a continuous variable. A possible explanation for these contradictory results could be attributed to the multiple variables (prostatic length, height and width) contributing to the prostatic volume which is then compared to body weight in the study by Spada et al [11], whereas in the current study (as well as in the mentioned studies by Haverkamp et al [18] and Delaude et al [12]), the different linear dimensions are compared separately with the dogs' body weight. Instead of a single measurement, with a single possibility for measurement error, each of the multiple measurements poses a risk for an additional measurement error.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Several studies have examined the influence of body weight on prostatic parameters, especially the gland size. 11,25,[35][36][37] Bosma et al 38 reported a significant correlation between body weight and single prostatic size parameters, such as length, height, and depth in castrated dogs, unlike our previous report which did not show any association between prostate volume and size of the dog. 15 Furthermore, the present study found a positive correlation between age at castration and TTP, which may reflect an influence of the timing of exposure to gonadal hormones on prostate vascularization appearance after castration.…”
Section: Discussioncontrasting
confidence: 78%
“…Several studies have examined the influence of body weight on prostatic parameters, especially the gland size 11,25,35–37 . Bosma et al 38 .…”
Section: Discussionmentioning
confidence: 99%